2010
DOI: 10.1167/10.8.18
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism between fine and coarse motion sensors depends on stimulus size and contrast

Abstract: The perceived direction of motion of a brief visual stimulus that contains fine features reverses if static coarser features are added to it. Here we show that the reversal in perceived direction disappears if the stimulus is reduced in size from 2.8 deg to 0.35 deg radius. We show that for a stimulus with 1.4 deg radius, the reversals occur when the ratio between the contrast of the fine features and of the coarser features is higher than 0.8 and lower than 4. For stimulus with 0.35 deg radius, the reversals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 23 publications
3
10
0
Order By: Relevance
“…These results are in the same direction as previous results (Serrano-Pedraza et al, 2007;Serrano-Pedraza & Derrington, 2010). In effect, previous results have shown that the percentage of errors in direction discrimination increased with increasing size (Serrano-Pedraza & Derrington, 2010).…”
Section: Experiments 1 Suppression and Facilitation Ratios For Simplesupporting
confidence: 90%
See 2 more Smart Citations
“…These results are in the same direction as previous results (Serrano-Pedraza et al, 2007;Serrano-Pedraza & Derrington, 2010). In effect, previous results have shown that the percentage of errors in direction discrimination increased with increasing size (Serrano-Pedraza & Derrington, 2010).…”
Section: Experiments 1 Suppression and Facilitation Ratios For Simplesupporting
confidence: 90%
“…For the first time, we have measured duration thresholds for complex stimuli composed of fine and coarse scales. The duration-threshold measurements allowed us to characterize in stimulus terms a phenomenon that has been reported in performance terms in previous studies (Derrington & Henning, 1987;Henning & Derrington, 1988;Derrington et al, 1993;Serrano-Pedraza et al, 2007;Serrano-Pedraza & Derrington, 2010). In those studies, the authors fixed the presentation durations of the complex stimulus and measured the proportion of correct responses for direction discrimination as a function of the duration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Are the results of Serrano-Pedraza and Derrington (2010) related to ours? The model they propose takes the MAX response across noiseless and mutually suppressive mechanisms sensitive to different spatial frequencies.…”
Section: Discussionsupporting
confidence: 76%
“…Serrano-Pedraza and Derrington (2010) judged perceived direction of motion for a 3 c/deg Gabor target moving at 4 deg/sec, superimposed on a static 1 c/deg Gabor mask. When the stimulus was quite large (3.3° full width at half-height [FWHH]), the psychometric function relating target contrast to proportion of correct direction judgements was steep and nonmonotonic, with a similar form to those in Figure 3.…”
Section: Discussionmentioning
confidence: 99%